2023
DOI: 10.3390/polym15040840
|View full text |Cite
|
Sign up to set email alerts
|

Research on Low-Velocity Impact Response of Novel Short-Fiber-Reinforced Composite Laminates

Abstract: Short-fiber-reinforced polymers (SFRPs) based on unidirectionally arrayed chopped strands (UACSs) have excellent formability and outstanding mechanical response. The low-velocity impact response, such as the delamination, damage tolerance and energy absorption of UACS composites, are essential to guarantee the stability and safety of composite components in service. The current study investigates the low-velocity impact response of continuous carbon-fiber-reinforced polymer (CFRP) and UACS laminates with verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…UACS laminates with two different slit sizes were prepared for LVI experiments to compare their impact performance with that of UACS laminates with 25 mm slits that had been tested. 36 The structure diagram of UACS laminates with vertical slit sizes of 5, 10, and 25 mm, respectively, is illustrated in Figure 1. All the specimens were prepared with a stacking sequence of [0/90] 4s and a 2 mm thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UACS laminates with two different slit sizes were prepared for LVI experiments to compare their impact performance with that of UACS laminates with 25 mm slits that had been tested. 36 The structure diagram of UACS laminates with vertical slit sizes of 5, 10, and 25 mm, respectively, is illustrated in Figure 1. All the specimens were prepared with a stacking sequence of [0/90] 4s and a 2 mm thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Regular vertical slits were introduced in unidirectional CFRP prepreg utilizing a numerical control cutting machine. UACS laminates with two different slit sizes were prepared for LVI experiments to compare their impact performance with that of UACS laminates with 25 mm slits that had been tested 36 . The structure diagram of UACS laminates with vertical slit sizes of 5, 10, and 25 mm, respectively, is illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In order to precisely simulate the impact damage of woven fabric reinforced composites, Wu et al [26] developed yarn-level finite element models of hybrid 3D carbon/glass woven orthogonal composites, including failure criteria and progressive damage behavior. Huang et al [27] simulated the effect of slits filled with resin on the impact properties of unidirectionally arrayed chopped carbon fiber reinforced composites by using the Johnson-Cook material and failure model to describe the elastic-plastic property of the slits in the finite element models and found that the slits had a negative effect on the load-bearing capacity but increased the energy absorption. The aforementioned research shows that finite element modeling is an effective way to simulate and analyze the damage mechanism of woven fabric reinforced composites under low-velocity impact by introducing accurate failure criteria and progressive damage behavior and building an appropriate geometric model.…”
Section: Introductionmentioning
confidence: 99%